The Relationship Between Argumentative Speaking and Writing among EFL Students - Fouad Akki; Mohammed Larouz; Brahim Ait Hammou; Handoko Handoko (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
This study looks at the connection between argumentative writing and speaking among sixth-semester EFL students at Moulay Ismail University in Morocco’s English Studies department. In order to achieve this objective, a total of 80 undergraduate students who were learning English as a foreign language (EFL) were selected as participants. Participants were then given both speaking and writing examinations to assess their argumentation skills in these two areas. Regression and correlation analyses were performed in SPSS on the study’s data. The findings show a substantial difference between speaking and writing in contentious discourse, in addition to a high positive association. Argumentative speaking was statistically proven to predict a great proportion of argumentative writing. The findings suggest integrating argumentative speaking and writing in teaching and assessment practices in a balanced way. The two skills can be taught along with each other to facilitate correspondences between the two modalities in argumentative genre. As the study concludes, it offers valuable insights into the implications of these findings, highlights the research limitations encountered during the research process, and provides recommendations for future endeavors in the realm of language pedagogy and assessment. This study not only contributes to our understanding of the interplay between argumentative writing and speaking but also paves the way for more comprehensive and integrated language instruction practices in EFL contexts.